Surat Keterangan Waris Yang Memuat Keterangan Tidak Benar Dikaitkan Dengan Kekuatan Pembuktiannya Sebagai Akta Otentik - Shaﬁra Meidina Rafaldini; Anita Afriana; Pupung Faisal (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
In Indonesia the distribution of inheritance, there are often disputes between parties who have an interest in each other. This makes some people choose to make a Inher itance Certiﬁcate which aims to prove the parties entitled to inheritance from the testator. In practice, heirs are often found that contain incorrect statements and serve as evidence in court proceedings, as found in Supreme Court Decision Number 121/Pid/2017/PT.DKI. This article discusses the power of proof of authentic deeds which contain incorrect statements in terms of the perspective of the Civil Procedure Code and the validity of an agreement based on authentic deeds which contain incorrect statements based on the Civil Code. Normative juridical research methods are used in this study, namely in-depth analysis of the positive regulations concerned and also ﬁeld research related to the process of making a Certiﬁcate of Inheritance in the Religious Courts, Notaries, and Village Ofﬁ ce. Based on the results showed the Inheritance Certiﬁcate containing incorrect information, still has the power of proof attached as long as no cancellation is submitted to the judge by the parties who feel disadvantaged, and as long as there is no decision from the court stating that the deed is invalid. However, if there has been a decision from a judge stating that a certain authentic deed is invalid, then the deed no longer has the perfect proof of strength as an authentic deed.